2015
DOI: 10.1038/ncomms8394
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Θ is a key driver of genome evolution and of CRISPR/Cas9-mediated mutagenesis

Abstract: Cells are protected from toxic DNA double-stranded breaks (DSBs) by a number of DNA repair mechanisms, including some that are intrinsically error prone, thus resulting in mutations. To what extent these mechanisms contribute to evolutionary diversification remains unknown. Here, we demonstrate that the A-family polymerase theta (POLQ) is a major driver of inheritable genomic alterations in Caenorhabditis elegans. Unlike somatic cells, which use non-homologous end joining (NHEJ) to repair DNA transposon-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 53 publications
6
97
0
Order By: Relevance
“…TMEJ is thus a less effective competitor than is NHEJ for repair of DSBs, at least when the DSBs are destined for successful repair. A similar lack of effect of Pol θ deficiency on repair by HR is evident in C. elegans (van Schendel et al, 2015). Pol θ loss is nevertheless sufficient to stimulate IR-dependent Rad51 foci (Ceccaldi et al, 2015; Mateos-Gomez et al, 2015) (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…TMEJ is thus a less effective competitor than is NHEJ for repair of DSBs, at least when the DSBs are destined for successful repair. A similar lack of effect of Pol θ deficiency on repair by HR is evident in C. elegans (van Schendel et al, 2015). Pol θ loss is nevertheless sufficient to stimulate IR-dependent Rad51 foci (Ceccaldi et al, 2015; Mateos-Gomez et al, 2015) (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Alt-EJ is often considered to be a backup pathway that is active when C-NHEJ components are not available (Frit et al, 2014; Lin et al, 2013; Mladenov and Iliakis, 2011), but several lines of evidence indicate that alt-EJ repair occurs more frequently than previously thought, and can be the preferred method of repair in some situations (Ceccaldi et al, 2015; Gigi et al, 2014; Mateos-Gomez et al, 2015; Truong et al, 2013; van Schendel et al, 2015). For example, alt-EJ becomes the predominant repair pathway in mammalian cancer cells when HDR components are missing (Ceccaldi et al, 2015), and it can be induced by telomere de-protection (Mateos-Gomez et al, 2015) or the loss of C-NHEJ proteins (Bennardo et al, 2008; Secretan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila Polq ortholog Mus308 is responsible for alt-EJ (Chan et al, 2010; Yu and McVey, 2010), but its absence results in DNA repair through C-NHEJ, making alt-EJ dispensable for survival after DSBs (Chan et al, 2010). By contrast, in Caenorhabditis elegans, Polq and alt-EJ are essential for DSB repair in germ cells (van Schendel et al, 2015), while C-NHEJ is thought to be the dominant repair pathway in somatic tissues (Pontier and Tijsterman, 2009; Robert and Bessereau, 2007; van Schendel et al, 2015). Taken together, the studies in cancer cells and invertebrates indicate that under some circumstances Polq-mediated alt-EJ is more prevalent than the C-NHEJ (Sfeir and Symington, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that the DL238 and QX1211 haplotypes were highly divergent from the N2 reference, and that major genomic rearrangements may have occurred. To resolve the genomic structure of the s up-35/pha-1 element in these isolates, we de novo assembled the genomes of DL238 and QX1211 using a combination of our and previously published Illumina short reads (23, 24), followed by targeted Sanger sequencing to resolve repetitive regions and confirm scaffolds. The de novo assemblies confirmed that pha-1 is absent from DL238 and is highly pseudogenized in QX1211, and that sup-35 is pseudogenized in both (Fig.…”
Section: Dl238 and Qx1211 Carry An Ancestral Sup-35/pha-1 Haplotypementioning
confidence: 99%